Analysis of five texts using Russian formalist framework - Zainul, Nur Hidayah (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aimed to analyse the plot in relation to the characters found in the selected texts. The objectives are to unravel the extent to which the plot and characters of the selected serial texts conform to the framework used and to investigate how consistent this plot arrangement throughout the texts. The five texts selected for the purpose of this study were written by Lemony Snicket from The Series of Unfortunate Events. The texts “Book the Second: The Reptile Room” (1999), “Book the Forth: The Miserable Mill” (2000), “Book the Sixth: The Ersatz Elevator” (2001), “Book the Eight: The Hostile Hospital” (2001) and “Book the Tenth: The Slippery Slope” (2003) are stories that contain the spheres which are the main subject of the analysis. These spheres; villain, helper, donor, sought-for person, and hero are elaborated in Russian Formalist framework, the theory in which was applied in conducting the textual analysis of plot in relation to characters in the study. The findings revealed that the plots and characters of the texts studied still conform to the framework which was first used by Vladimir Propp on fairy tales even if they do not belong to the same genre as the fairy tales. Nevertheless, only five spheres were found in the texts studied suggesting that not all spheres can work in any story. The plot identified is also consistent throughout the series of texts whereby each of them followed the same pattern described in the framework.